Effect of Depth Order on Linear Vection with Optical Flows. (December 2014) - Seya, Yasuhiro; Tsuji, Takayuki; Shinoda, Hiroyuki
In the present study, the effects of depth order on forward and backward vection were examined using optical flows simulating motion in depth (i.e., approaching or receding). In an experiment, space extending 10 or 20 m in depth was simulated, and the space was divided into foreground and background spaces. In each space, a random-dot pattern was presented and the binocular disparity, size, and velocity of each dot were continuously manipulated in a way consistent with the depth being simulated. Participants reported whether they perceived vection. Latency, total duration (i.e., the amount of time that participants reported perceiving vection during a 60-s presentation), and strong-vection duration (i.e., the amount of time that participants reported perceiving strong vection) were measured. The results indicated that, even though the dots making up the optical flow were much smaller and slower moving in the background space than in the foreground space, vection was strongly dependent on flow motion in the background space. This supports the idea that the perceptual system uses background stimulus motion as a reliable cue for self-motion perception.